2021
DOI: 10.1210/jendso/bvab048.340
|View full text |Cite
|
Sign up to set email alerts
|

Novel Germline SUCLG2 Mutations in Patients With Pheochromocytoma and Paraganglioma

Abstract: Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors derived from neural crest cells that are frequently linked to mutations including those in Krebs cycle enzymes, particularly succinate dehydrogenase (SDH). Succinyl-CoA ligase (SUCL) catalyzes reversible conversion of succinyl-CoA to succinate providing the substrate for SDH. While mitochondrial diseases were documented for the mutations in SUCL subunits G1 and A2, the association of GDP/GTP-specific subunit SUCLG2 mutations with speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Patient Samples: Fresh LUAD tissues and adjacent normal tissues were obtained from the First Affiliated Hospital of Nanchang University with approval from the Medical Research Ethics Committee of the First Affiliated Hospital of Nanchang University (2020) CDYFYYLK (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). All samples were collected with the patients' informed consent and frozen and preserved at −80 °C for subsequent experimental analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Patient Samples: Fresh LUAD tissues and adjacent normal tissues were obtained from the First Affiliated Hospital of Nanchang University with approval from the Medical Research Ethics Committee of the First Affiliated Hospital of Nanchang University (2020) CDYFYYLK (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). All samples were collected with the patients' informed consent and frozen and preserved at −80 °C for subsequent experimental analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, SUCLG2 has been identified as a novel candidate gene in hereditary PPGL. In the work of Vanova et al 2021, SUCLG2-mutated PPGL tumors and SUCLG2-deficient chromaffin cells revealed the decrease in the level of the SDHB subunit of SDH, and faulty assembly of the complex II, resulting in aberrant respiration and elevated succinate accumulation [24].…”
Section: Pseudohypoxic Clustermentioning
confidence: 99%
“…Within the context of certain PPGLs, genetic perturbations affecting enzymes integral to the TCA cycle, such as SDH and FH, emerge as salient features (56). Since the initial discovery in 2000 of the correlation between SDHD germline mutations and familial paragangliomatosis, a growing compendium has cataloged mutations within at least twelve TCA cycle-related genes in the landscape of PPGLs (SDHB, SDH, SDHC, SDHD, SDHAF2, FH, IDH1, MDH2, SUCLG2, DLST, SLC25A11, and GOT2) (8,57,58). Among these, SDHx, FH, IDH1, and MDH2 have garnered relatively more attention, with mutations within SDHx and FH, in particular, emerging as pivotal drivers in the genesis and Regulation of HIFa (HIF-1a/HIF-2a) by the PHD/VHL Pathway and Impact of Tricarboxylic Acid Cycle Metabolic Mutations.…”
Section: The Tca Cycle and Ppglsmentioning
confidence: 99%